2017
DOI: 10.3390/ijms18071367
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Zfp217 in Adipogenesis

Abstract: Zinc finger protein 217 (Zfp217), a member of the krüppel-type zinc finger protein family, plays diverse roles in cell differentiation and development of mammals. Despite extensive research on the functions of Zfp217 in cancer, pluripotency and reprogramming, its physiological roles in adipogenesis remain unknown. Our previous RNA sequencing data suggest the involvement of Zfp217 in adipogenesis. In this study, the potential function of Zfp217 in adipogenesis was investigated through bioinformatics analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Our previous study showed that Zfp217 is positively correlated with triglyce cumulation and can promote fat accumulation through post-transcriptional modi of m6A [25,27]. Similarly, we found that Zfp217 deletion causes resistance to H duced obesity in in vivo experiments, possibly due to reduced adipogenesis or in those of Zfp217 +/+ mice (Figure 5A).…”
Section: Impact Of Zfp217 Deletion On Gene Expression In Inguinal Adipose Tissuesupporting
confidence: 74%
See 1 more Smart Citation
“…Our previous study showed that Zfp217 is positively correlated with triglyce cumulation and can promote fat accumulation through post-transcriptional modi of m6A [25,27]. Similarly, we found that Zfp217 deletion causes resistance to H duced obesity in in vivo experiments, possibly due to reduced adipogenesis or in those of Zfp217 +/+ mice (Figure 5A).…”
Section: Impact Of Zfp217 Deletion On Gene Expression In Inguinal Adipose Tissuesupporting
confidence: 74%
“…Zinc Finger Protein 217 (Zfp217) belongs to the Krüppel-type transcription factors [24]. Recent studies have revealed that Zfp217 is also involved in adipogenesis, through interaction with histone methylation enzyme EZH2 to promote adipogenesis by influencing cell cycle [25]; through the interaction of Zfp217 and m6A methyltransferase METTL3 or demethylase FTO, the m6A modification level of related downstream target genes is influenced and mediates post-transcriptional modifications of m6A in a YTHDF2-dependent manner, thereby affecting adipocyte differentiation, suggesting that Zfp217 could play an important role in adipogenesis at the level of transcription and post-transcriptional modifications [26,27]. However, the function of Zfp217 in in vivo animal models is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, Zfp217 tightly couples gene transcription with m 6 A modification on the nascent RNA, suggesting a key role for Zfp217 in coordinating epigenetic and epitranscriptomic networks (8,22). While we previously identified a novel role for Zfp217 in adipogenesis, a detailed Zfp217-dependent mechanism has not been well characterized (23,24). However, these studies raise the possibility that Zfp217 may modulate the m 6 A modification to accelerate adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[32] However, in vivo model of conditional knockout of BCL6 in adipose tissues showed that BCL6 deletion would lead to WAT expansion, [33] implying that BCL6 possibly plays different roles in regulating early adipogenesis and late lipogenesis. From some RNA-seq data used to identify BCL6, we have also identified a novel transcription factor Zfp217 that regulates early adipogenesis of C3H10T1/2 cell line [25,34] (Figure 2), implying that the transcriptional atlas of commitment can be further improved. In addition, another group identified a repressor of adipogenesis from zinc finger protein family, namely, Zfp521, [35] which acts as a paralog of Zfp423 and inhibits commitment by binding to Ebf1 to block the expression of Zfp423 (Figure 2).…”
Section: Transcription Factors Regulating Commitmentmentioning
confidence: 99%